The Emergence of Cross Channel Scripting. - Bojinov, Hristo; Bursztein, Elie; Boneh, Dan (Communications of the ACM, 2010)
Lightweight, embedded Web servers are soon about to outnumber regular Internet Web servers. They reside in devices entrusted with personal and corporate data, and are typically used for configuration and management. We reveal a series of attacks on consumer and small office electronics, ranging from networked storage to digital photo frames. The attacks target Web server logic and are based on a new type of vulnerability that we call cross channel scripting (XCS). XCS is a sophisticated form of cross site scripting (XSS) in which the attack injection and execution are carried out via different protocols.